Railway engineer Yu. V. Lomonosov about scientific problems of railways’ operation - O. H. Strelko (History of science and technology, 2014)
The article highlights the contribution of professor, outstanding national railway engineer,Yurii Volodymyrovych Lomonosov (1876-1952), the scientist in the field of trains‟ traction, the interaction of the rolling stock and track and railways‟ operation. He created the “Office on locomotives‟ investigation” (1912-1917). Under Yu. V. Lomonosov „s leadership the draft of one of the first national diesel locomotives (built in Germany in 1924) has been developed. In the 1918-1920 s Yu. V. Lomonosov was the member of the board in the People‟s Commissariat of Communications. In the 1920-1923 s – he became the head of the Russian railway mission for locomotives‟ purchase abroad. He has lived abroad since 1927. His scientific works are devoted to the investigation of trains‟ traction, rolling stock tests, and scientific fundamentals of railways‟ operation.